What Do You Need to Know before Studying Chagas Disease? A Beginner’s Guide - José A. De Fuentes-Vicente; Nancy G. Santos-Hernández; Christian Ruiz-Castillejos; Eduardo E. Espinoza-Medinilla; A. Laura Flores-Villegas; Mariana de Alba-Alvarado; Margarita Cabrera-Bravo; Adriana Moreno-Rodríguez; Dolores G. Vidal-López (Tropical Medicine and Infectious Disease, 2023)
Chagas disease is one of the most important tropical infections in the world and mainly affects poor people. The causative agent is the hemoflagellate protozoan Trypanosoma cruzi, which circulates among insect vectors and mammals throughout the Americas. A large body of research on Chagas disease has shown the complexity of this zoonosis, and controlling it remains a challenge for public health systems. Although knowledge of Chagas disease has advanced greatly, there are still many gaps, and it is necessary to continue generating basic and applied research to create more effective control strategies. The aim of this review is to provide up-to-date information on the components of Chagas disease and highlight current trends in research. We hope that this review will be a starting point for beginners and facilitate the search for more specific information.